2020
DOI: 10.1007/s00431-020-03827-w
|View full text |Cite
|
Sign up to set email alerts
|

Video discharge instructions for pediatric gastroenteritis in an emergency department: a randomized, controlled trial

Abstract: The aim was to evaluate if the addition of video discharge instructions (VDIs) to usual verbal information improved the comprehension of information provided to caregivers of patients who consult for acute gastroenteritis (AGE). We conducted an open-label, parallel, randomized trial, enrolling patients who consulted for AGE at a tertiary hospital. First, caregivers answered a written test concerning AGE characteristics and management. They were randomly allocated to a control group, which received the usual ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…The results of this study are in line with research on video-based discharge planning instructions for pediatric gastroenteritis in the emergency department, the results show that when families receive video discharge instructions, the level of knowledge and skills of families caring for patients in hospitals increases compared to caregivers who only receive verbal instructions (Jové-Blanco et al, 2021;Suwardianto & Astuti, 2020;. These results are consistent with those obtained by Redzuan et al (2013) where the addition of video instructions about the response to diseases experienced by patients such as fever and headaches increased family knowledge after returning home.…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study are in line with research on video-based discharge planning instructions for pediatric gastroenteritis in the emergency department, the results show that when families receive video discharge instructions, the level of knowledge and skills of families caring for patients in hospitals increases compared to caregivers who only receive verbal instructions (Jové-Blanco et al, 2021;Suwardianto & Astuti, 2020;. These results are consistent with those obtained by Redzuan et al (2013) where the addition of video instructions about the response to diseases experienced by patients such as fever and headaches increased family knowledge after returning home.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, the methodological quality of the studies varied: 30% (11/37) of the studies met ≤60% of the criteria outlined by the MMAT (lower methodological quality), and 70% (26/37) of the studies met >60% of the criteria (higher methodological quality) [ 26 ]. Reviewers’ ratings for each methodological quality criterion are presented in Multimedia Appendix 2 [ 28 - 33 , 35 - 39 , 41 - 46 , 49 - 51 , 54 - 66 , 68 , 73 , 74 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Text message interventions were more likely to be measured on behavioral outcomes (eg, compliance with medication regime and follow-up appointment with primary care), whereas studies of video-based EDCTs typically used knowledge acquisition–related measures. A randomized controlled trial by Jové-Blanco et al [ 46 ] comparing video discharge instructions and standard verbal instructions for gastroenteritis showed that 49% of the intervention group and 18.6% of the control group answered all knowledge acquisition questions correctly ( P <.001) [ 48 ]. However, EDCTs with greater technological sophistication do not always produce better knowledge outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of utmost importance that written discharge instructions, which often score poorly on assessments of understandability, be at an appropriate reading level 14 19. Finally, use of bedside communication adjuncts such as white boards20 and videos21 22 have also proven helpful.…”
Section: Discussionmentioning
confidence: 99%